Bilateral elastofibroma dorsi: a case report of an uncommon and under-diagnosed tumor - Braun, Stefanie; Richter, Matthias; Ernst, Tom; Flade, Andreas; Uhlmann, Dirk (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Elastofibroma dorsi is a rare benign tumor of the back, located between the latissimus dorsi and the rhomboid muscle. In most cases it is unilateral, but in up to 10% it occurs on both sides. The etiology is still in discussion. Here we report a case of a 51-year-old man with bilateral elastofibroma dorsi. The therapy of choice was surgical resection. No long-term complications were reported in a 6-month follow-up.